Degradation of polymeric power cable due to water treeing under AC and DC stress - Arief, Yanuar Zulardiansyah (2012)
Water treeing is a well known phenomenon in polymeric cables, where it plays an important role in insulation ageing and degradation process of the material. Water treeing had been investigated for three decades and the level of investigation of water treeing field on electrical insulation has grown considerably especially in polymeric power cable. One of the polymeric insulation materials, named crosslink polyethylene (XLPE) has been widely used as insulation material in power cables. This project focuses more on analysis of insulation parameters such as insulation resistance, tan δ (delta), power factor, capacitance and return voltage profile in 1 kV aged XLPE cable due to water trees under AC and DC stress. As a result, water treeing affects the insulation degradation of polymeric power cable and influences other insulation parameters such as insulation resistance, tan δ, power factor, capacitance, and voltage recovery profile. The value of insulation resistance and capacitance decreased while the value of power factor and tan d increased after injection of 2 kV AC voltage, due to water treeing for certain ageing time.